2012
DOI: 10.1002/arch.21019
|View full text |Cite
|
Sign up to set email alerts
|

DIFFERENTIAL EXPRESSION OF THE Bombyx mori DIAPAUSE‐TERMINATION TIMER GENE Ea4 IN DIAPAUSE‐INDUCING TEMPERATURE AND PHOTOPERIOD

Abstract: Diapause in Bombyx mori eggs is induced by temperature and photoperiod at the stage of embryonic development in the maternal generation. In those diapause eggs, Esterase-A4 is suggested to serve as a diapause-termination timer (TIME-EA4), because its ATPase activity shows an interval-timer elevation after acid treatment or chilling of eggs to break diapause. To clarify whether the timed ATPase activity of TIME-EA4 is related to its gene (Ea4) expression, we analyzed Ea4 mRNA of eggs in diapause-inducing enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Therefore, we inferred that BmChsB is a gene expressed specifically in the midgut. Its feeble expression in gonads is actually a very common phenomenon shared by many tissue‐specific genes of the silkworm (Gan et al., ; Xu et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we inferred that BmChsB is a gene expressed specifically in the midgut. Its feeble expression in gonads is actually a very common phenomenon shared by many tissue‐specific genes of the silkworm (Gan et al., ; Xu et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we inferred that BmChsB is a gene expressed specifically in the midgut. Its feeble expression in gonads is actually a very common phenomenon shared by many tissue-specific genes of the silkworm (Gan et al, 2010;Xu et al, 2012). Based on the findings described above, we investigated the BmChsB expression profiles in the midgut during molting and the mulberry-leaf ingestion processes.…”
Section: Archives Of Insect Biochemistry and Physiologymentioning
confidence: 99%
“…In recent years, many studies have focused on the effects of lighting on animal behavior and internal physiology and metabolism at the genetic and protein levels (Edery, 2000;Glaser and Stanewsky, 2005;Lohmann et al, 2007;Fuller et al, 2008). Insects are cold-blooded, thus temperature is directly involved in the regulation of physiological behavior mechanisms including hatching and feeding, growth and metamorphosis, reproduction and diapause, and migration and calling (Zhu et al, 2008a(Zhu et al, /2008bTanaka and Watari, 2011;Xu et al, 2012;Hosseinzade et al, 2014;Liao et al, 2014;Soltani Orang et al, 2014). A Drosophila study found that cyclical changes in temperature with differences of 2-3°C reset and synchronized the circadian clock (Gentile et al, 2013).…”
Section: Introductionmentioning
confidence: 99%